"Fake it until you make it": business model conceptualization in digital entrepreneurship. (4th July 2018) - Standing, Craig; Mattsson, Jan
Abstract: Digital business model research spans the disciplines of information systems, marketing and entrepreneurship. Despite the growing research in the area there is a lack of understanding of how digital entrepreneurs identify business opportunities and conceptualize those in a business model. The literature on business models lacks consistent terminology and specification of critical components. Through an explorative study of digital entrepreneurs we examine how entrepreneurs identify business opportunities and how they translate them into a workable business idea. Although entrepreneurs typically have difficulty explaining their business model components we identified that critical features in our simplicity framework include three main modules, transaction/matching, marketing and back-office components, and simplicity in terms of value proposition, conceptualization approach and usability. This research proposes that a parsimonious view of digital business models, aligned with the lean start-up idea, makes sense for theory development and in terms of usefulness for entrepreneurs.